Culinary Tourism and Visit Intention at Kukup Beach, Indonesia - Aneke Rahmawati; Suci Sumbawati (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
Culinary tourism has become an increasingly important component of tourism development, particularly as a core tourism product that shapes tourists’ experiences and behavioral intentions in coastal destinations. In Indonesia, coastal culinary experiences based on seafood play a strategic role in shaping tourists’ perceptions and consumption patterns. This study focuses on culinary tourism and examines its influence on tourists’ visit intention at Kukup Beach, Gunungkidul Regency, Indonesia. A quantitative associative research design was employed using a survey method. Data were collected from 35 tourists through structured questionnaires measured on a five-point Likert scale. Descriptive statistical analysis, Pearson correlation, and simple linear regression were applied to analyze the data. The results show a positive and statistically significant relationship between culinary tourism and tourists’ visit intention (r = 0.579; p < 0.05). Culinary tourism explains 33.56% of the variance in visit intention, indicating that food quality, variety, hygiene, service quality, and price fairness are important determinants of tourists’ intention to revisit and recommend the destination. This study contributes empirical evidence to culinary tourism research in coastal destinations and provides practical implications for destination managers in integrating local culinary products into sustainable tourism development strategies.